The voice of God - Jacobs, Cindy, 1951- (Ventura, Calif., USA : Regal Books, 1995)
Christian Library of Lancaster Collection.
Includes bibliographical references (p. [260]-262) and indexes.
Keywords: Prophecy -- Christianity; Spiritual warfare